Competitive Cortical Prioritization Emerges for Trained Objects across the First Year of Life - Boylan, Maeve R; Tebbe, Anna-Lena; Newland, Jamie; Sanches Braga Figueira, Jessica; Keil, Andreas; Scott, Lisa S (The Journal of neuroscience, 2025)
Learning to detect and recognize a broad range of visual objects is a crucial developmental task during the first year of life. However, many of the neurophysiological changes underlying the emergence of this cognitive ability remain poorly understood. The current study tested the hypothesis that training infants to recognize novel objects leads to selectively enhanced visuocortical responses and a competitive advantage that prioritizes the processing of trained relative to untrained objects. A cross-sectional sample of parent-infant dyads at 6, 9, and 12 months of age read books in which novel objects were associated with different types of labels. The next day, EEG was recorded while infants ( = 51, 24 females and 26 males, 1 unknown) were concurrently presented with trained objects (i.e., from the book) and untrained objects (i.e., novel objects not in the book). Trained and untrained objects flickered at distinct frequencies (5 Hz, 6 Hz) to evoke frequency-tagged steady-state visual evoked potentials (ssVEPs). Analyses of the visuocortical response showed training-related competition effects that increased with age. Specifically, responses to trained stimuli increased while responses to untrained stimuli decreased with age. At 6 months, infants showed no visuocortical bias for trained objects, but by 9 and 12 months, visuocortical responses favored trained objects. This pattern suggests that competitive neural interactions between trained and untrained stimuli may support the development of object recognition and that experience with objects guides attentional prioritization in the infant brain.